Yokukansan improves behavioral and psychological symptoms of dementia by suppressing dopaminergic function - Takeyoshi K; Kurita M; Nishino S; Teranishi M; Numata Y; Sato T; Okubo Y (Neuropsychiatric Disease and Treatment, 2016)
Kenji Takeyoshi,1,2 Masatake Kurita,1–3 Satoshi Nishino,2,3 Mika Teranishi,1 Yukio Numata,2 Tadahiro Sato,2 Yoshiro Okubo11Department of Psychiatry and Behavioral Science, Graduate School of Medicine, Nippon Medical School, Bunkyo-ku, Tokyo, 2Sato Hospital, Koutokukai, Nanyo, Yamagata, 3Department of Cellular Signaling, Graduate School of Pharmaceutical Sciences, Tohoku University, Sendai, Miyagi, JapanAbstract: Although three drugs, risperidone, yokukansan, and fluvoxamine, have shown equal efficacy in treating behavioral and psychological symptoms of dementia (BPSD) in our previous study, their mechanisms of action are different from one another. Monoamines have attracted attention for their key roles in mediating several behavioral symptoms or psychological symptoms through synaptic signaling. We aimed to clarify the monoamines changed by treatment with each drug in patients with BPSD. The main purpose of this study was to determine whether plasma levels of catecholamine metabolites are correlated with pharmacological treatments. This was an 8-week, rater-blinded, randomized, flexible-dose, triple-group trial. In total, 90 subjects were recruited and subsequently three different drugs were allocated to 82 inpatients with BPSD. We examined BPSD data from patients who completed 8 weeks of treatment. Eventually, we analyzed 42 patients (yokukansan: 17; risperidone: 9; fluvoxamine: 16). Homovanillic acid, a metabolite of dopamine, and 3-methoxy-4-hydroxyphenylglycol, a metabolite of noradrenaline, in their plasma were analyzed by high-performance liquid chromatography with electrochemical detection. All three drugs showed equal significant efficacy between baseline and study endpoint. By contrast, biomarkers showed mutually different changes. Patients in the yokukansan group had significantly decreased plasma homovanillic acid levels from baseline. Conversely, patients in the risperidone and fluvoxamine groups exhibited no significant changes in plasma homovanillic acid levels from baseline. Yokukansan contains geissoschizine methyl ether, which is known to have a partial agonist effect on dopamine D2 receptors. An improvement in BPSD condition with the intake of yokukansan is suggested to occur through a suppressed dopaminergic function, which is similar to the effect of aripiprazole.Keywords: herbal medicine, MHPG, homovanillic acid, HVA, noradrenaline, BPSD